Effect of Soybean Variety and Heating Time on The Chemical and Physical Characteristics of ‘Yuba’ Edible Film - Saparianti, Ella (Jurnal Teknologi Pertanian, 2005)
The research was conducted to study the effect of soybean variety and heating time in producing ‘yuba’ as an edible film. Completely Randomized Block Design (CRBD) was employed in the experiment with two factors and three replicates.  The first factor was   soybean varieties i.e. Willis 2000 (a local variety) and AS (an imported soybean variety from USA). The second factor was the heating time:15, 30, 45 and 60 minutes respectively. The results showed that the chemical characteristics of the ‘yuba’ were significantly affected by soybean varieties, but not by the heating time. The moisture, protein, and lipid contents of ‘yuba’ produced from the local  soybean variety were found to be higher than those of the ‘yuba’ made up of the imported soybean variety. Similarly, the physical characteristics of the ‘yuba’ were also significantly by soybean varieties. Except for the vapor permeability, the values of density, thickness, tensile strength, puncture strength, elongation of the local soybean ‘yuba’ were higher than those of  the ‘yuba’ made up of the imported soybean.   Key words : Yuba, edible film, local and imported soybean varieties